2009
DOI: 10.1016/j.ijid.2008.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Panton–Valentine leukocidin genes among carriage and invasive Staphylococcus aureus isolates in Malaysia

Abstract: Prevalence of Panton-Valentine leukocidin genes among carriage and invasive Staphylococcus aureus isolates in MalaysiaStaphylococcus aureus nasal colonization is common among humans, and causality between carriage and invasive diseases has been substantiated. 1 The pathogenicity of S. aureus is determined by a variety of bacterial cell wall surface components and exoproteins. Panton-Valentine leukocidin (PVL), one of these pathogenic determinants, is a bicomponent cytotoxin encoded by the pvl genes luk-S-PV an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
24
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 10 publications
7
24
1
Order By: Relevance
“…20 A more recent study reported that ST188 PVLpositive MSSA was predominant among discharge patients in Malaysia. 37 In concordance with other studies, we did not find PVLpositive MRSA in Indonesia. 20,36 However, the emergence of such strains is not unlikely because of possible horizontal transfer of the mecA gene to PVL-positive MSSA.…”
Section: Discussionsupporting
confidence: 93%
“…20 A more recent study reported that ST188 PVLpositive MSSA was predominant among discharge patients in Malaysia. 37 In concordance with other studies, we did not find PVLpositive MRSA in Indonesia. 20,36 However, the emergence of such strains is not unlikely because of possible horizontal transfer of the mecA gene to PVL-positive MSSA.…”
Section: Discussionsupporting
confidence: 93%
“…Additional studies are under way to investigate this further. Unlike other ST772-MRSA-V isolates reported in the literature (1,11,13,15,24,26,34), those recovered within the Irish maternity hospital NICU were not associated with any known clinical diagnosis of infection and were most frequently recovered from screening specimens of patients within the NICU. In contrast, the seven ST772-MRSA-V isolates recovered from patients in other Irish hospitals (n ϭ 2) and from patients in the community (n ϭ 5) and for which there was clinical information available were found to be associated with skin and soft tissue infections.…”
Section: Discussionmentioning
confidence: 63%
“…Recently, a PVL-positive CA-MRSA clone, ST772-MRSA-V, that is relatively multiantibiotic resistant compared to other CA-MRSA clones was identified in several countries. Methicillin-susceptible ST772 S. aureus was originally reported in Bangladesh, but this was quickly followed by reports of ST772-MRSA-V in India and Malaysia and subsequently in England, Italy, Australia, Germany, Hong Kong, and Abu Dhabi (1,13,15,24,26,34). Many patients identified with ST772-MRSA-V outside India had familial links in, or travel history to or from, India, resulting in the ST772-MRSA-V clone being dubbed the Bengal Bay clone (15,24,26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These newer variants also carry several toxins and virulence factors, including Panton-Valentine leukocidin (PVL). ST772, called the Bengal Bay clone by some, was previously reported only in Bangladesh, India, and Malaysia but is now being reported in England, Ireland, and several other European countries (1,4,10).…”
mentioning
confidence: 99%